Aza‐Piancatelli Cyclization as a Platform for the Preparation of Scaffolds of Natural Compounds: Application to the Total Synthesis of Bruceolline D. Issue 33 (25th August 2020) - Marin, Lucile; Force, Guillaume; Gandon, Vincent; Schulz, Emmanuelle; Lebœuf, David
Abstract : The aza‐Piancatelli cyclization provides an expedient synthesis of 4‐aminocyclopentenone building blocks that may be converted into aminocyclopentitols, which are heavily represented motifs among natural products. However, its use as a key step in total synthesis was still unprecedented. Here, we disclose our in‐depth investigations regarding this reaction in order to access highly complex structures representing the core of some natural molecules. The applicability of the cyclization was highlighted by the 3‐step total synthesis of bruceolline D. Thus, we anticipate that this work will lay the ground for further applications in total synthesis. Abstract : The aza‐Piancatelli cyclization provides a rapid and practical route to densely functionalized 4‐aminocyclopentenones from biomass‐derived 2‐furylcarbinols. Through a better understanding of the scope and limitations of this reaction, a 3‐step synthesis of bruceolline D was achieved.